2019
DOI: 10.1136/bmjhci-2019-100055
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral palsy information system with an approach to information architecture: a systematic review

Abstract: BackgroundLong-term complications and high costs of cerebral palsy (CP) as well as inconsistency in data related to this disease reveal the need for extensive planning to obtain accurate and complete data for the effective management of patients.ObjectiveThe present study reviews the information architecture of CP information system.MethodThe relevant articles published from early 1988 to 31 July 2018 were extracted through searching PubMed, Scopus, Cochran, Web of Science and Embase databases conducted indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 58 publications
0
10
0
1
Order By: Relevance
“…Jelenleg számos CP-regiszter működik világszerte, melyek többnyire egységes CP-osztályozási módszert követnek, a WHO 2004. évi ICF-(International Classification of Function, Health, and Disability) ajánlása alapján [12]. A súlyossági besorolás szempontjából az okozott korlátozottság a mérvadó, melyre a legelterjedtebb pontozási skála a vizsgálatunkban is használt GMFCS [13].…”
Section: Eredeti Közleményunclassified
“…Jelenleg számos CP-regiszter működik világszerte, melyek többnyire egységes CP-osztályozási módszert követnek, a WHO 2004. évi ICF-(International Classification of Function, Health, and Disability) ajánlása alapján [12]. A súlyossági besorolás szempontjából az okozott korlátozottság a mérvadó, melyre a legelterjedtebb pontozási skála a vizsgálatunkban is használt GMFCS [13].…”
Section: Eredeti Közleményunclassified
“…Cerebral palsy (CP) is a group of permanent disorders of the development of movement and posture that are considered one of the most frequent causes of non-progressive motor disability in children [1,2]. Symptoms of CP vary from person to person, ranging from mild to very severe movement difficulties [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral palsy (CP) is a group of permanent disorders of the development of movement and posture that are considered one of the most frequent causes of non-progressive motor disability in children [1,2]. Symptoms of CP vary from person to person, ranging from mild to very severe movement difficulties [1,2]. CP is a very diverse problem accompanied by multiple comorbidities such as communication impairment, cognitive impairment, visual and hearing impairment, reduced alertness, epilepsy, seizures, musculoskeletal problems, feeding difficulties, behavioral disorders, mental retardation, and even sleep disorders [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, recent studies in the United States, Taiwan, and Egypt have found rates above 3 per 1000 1,2 . Rates in low-and middle-income countries are uncertain; they appear to be higher, with projections of 4.4 to 10 cases per 1000 1 , probably due to higher burden of infectious diseases and deficiencies in prenatal and perinatal care 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the sequelae of this disorder affect individuals throughout their lives, most research efforts and management strategies focus on the needs of the pediatric population, their clinical management, and the prevention of secondary problems 1,3,4 . Resources must be justified in assessing needs, among which are those derived from developmental motor disorders, as they acquire relevance due to the negative impact on the quality of life of children, their families, and the community, and the disability burden they generate for health systems 1,[5][6][7] .…”
Section: Introductionmentioning
confidence: 99%